Teologi: Telaah dan Pembahasan Wahyu dan Iman Yang Hidup. Keprihatinan untuk Pendidikan Teologi di Era Sekularistik - St. Gitowiratmo (Jurnal Orientasi Baru, 2008)
Is theology in crisis of identity amid this modem world? In order to be able to answer such a question, we need to focus on and emphasize the role and contribution of Christian theology for the life of human being. Christian theology should be able to help people to understand basic human values in the light of correlation between God and human being. Such theology should be close to the people as well as contextual. For these purposes, theology needs to consider seriously its medium which are human languages and cultures. This modern and secularized age, unfortunately, also puts human languages and cultures in a crisis of meaning: a change from metaphysical and mystical expressions to a pragmatic and materialistic one. It does mean, positively, that Christian theology should be presented and communicated in a creative way and methodologically sound. This is a real challenge for a Christian theology in the modern world.